2023
DOI: 10.1002/dta.3469
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth metabolic study of nonsteroidal selective androgen receptor modulator GSK2881078 in thoroughbred horses and horse liver microsomes for doping control

Abstract: Nonsteroidal selective androgen receptor modulators (SARMs) are a novel class of compounds that have not yet been clinically approved; however, they appear to have a better anabolic/androgenic ratio than steroids and cause slighter side effects. Sports drug testing laboratories are required to maintain continuously updated doping control analytical methods in light of the widespread misuse of SARMs in elite and amateur sports. This paper describes the metabolic conversion of SARM GSK2881078 in thoroughbred hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Our previous studies on SARMs showed multiple adducts in both positive and negative ionization modes. [30][31][32][33] It is possible that the formation of multiple adducts will impact the sensitivity of the analysis and mislead the limit of detection (LOD). Finding the exact cause of adduct formation is necessary to decide which method is appropriate for analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies on SARMs showed multiple adducts in both positive and negative ionization modes. [30][31][32][33] It is possible that the formation of multiple adducts will impact the sensitivity of the analysis and mislead the limit of detection (LOD). Finding the exact cause of adduct formation is necessary to decide which method is appropriate for analysis.…”
mentioning
confidence: 99%
“…The aim of this study was to develop a screening method for nitrile functional groups containing SARMs and to investigate the impact of the formation of adducts. The formation of adducts was investigated in 10 SARMs (Figure 1), namely AC-262536, 34,35 ACP-105, 31,36 RAD140,37 LY2452473 (TT-701), 32,38 PF-06260414, 39 GLPG0492 (DT-200), 30,40 LGD-4033 (Ligandrol or VK5211), 41 GSK2881078, 33,42 Ostarine (Enobosarm or MK-2866), 43 and Bicalutamide (ICI-176334 or ZD-176334). 44 This set of molecules was thoroughly examined in both positive and negative ionization modes, allowing for the identification of the most suitable adduct species for each SARM.…”
mentioning
confidence: 99%